Constitutive Analysis and Microstructure Characteristics of As-Homogenized 2198 Al–Li Alloy under Different Hot Compression Deformation Conditions - Li, Huiyu; Li, Xiwu; Yan, Hongwei; Li, Yanan; Geng, Libo; Xun, Chenyang; Li, Zhihui; Zhang, Yongan; Xiong, Baiqing (Materials, 2023)
The 2198 Al–Li alloy has unique superiority in mechanical performance and has been extensively used in the aerospace field. In this study, the hot deformation behavior of the 2198 Al–Li alloy was investigated on a Gleeble-1500 thermomechanical simulator with a strain rate of 0.01–10 s−1 in the temperature range of 330–510 °C. The Arrhenius constitutive equation of the alloy was established based on the true stress–strain curves to describe the rheology behaviors during the deformation of the alloy. The processing maps under the strain of 0.2–0.8 were constructed, which indicates the efficiency of power dissipation and instability of the deformed alloy. It was found that the instability domains are more likely to occur in the regions of low deformation temperature and high strain rate, corresponding to the high Zener–Hollomon (Z) parameter. The microstructure evolution of the studied alloy with different Z parameters was characterized. Then, the dynamic recrystallization (DRX) behavior was studied by electron backscatter diffraction, and the misorientation angle of deformed specimens was analyzed. The effect of different deformation temperatures and strain rates on the microstructure of the alloy and the behavior of dislocations and precipitations were investigated by transmission electron microscopy. The results demonstrate that continuous dynamic recrystallization (CDRX) and geomatic dynamic recrystallization (GDRX) mainly occur at the deformation conditions of a low Z value, and discontinuous dynamic recrystallization (DDRX) is likely to occur with increasing Z values.